Arboreality drives heat tolerance while elevation drives cold tolerance in tropical rainforest ants. Issue 1 (21st November 2021) - Leahy, Lily; Scheffers, Brett R.; Williams, Stephen E.; Andersen, Alan N.
Abstract: Determining how species thermal limits correlate with climate is important for understanding biogeographic patterns and assessing vulnerability to climate change. Such analyses need to consider thermal gradients at multiple spatial scales. Here we relate thermal traits of rainforest ants to microclimate conditions from ground to canopy (microgeographic scale) along an elevation gradient (mesogeographic scale) and calculate warming tolerance to assess climate change vulnerability in the Australian Wet Tropics Bioregion. We test the thermal adaptation and thermal niche asymmetry hypotheses to explain interspecific patterns of thermal tolerance at these two spatial scales. We tested cold tolerance (CTmin ), heat tolerance (CTmax ), and calculated thermal tolerance range (CTrange ), using ramping assays for 74 colonies of 40 ant species collected from terrestrial and arboreal habitats at lowland and upland elevation sites and recorded microclimatic conditions for one year. Within sites, arboreal ants were exposed to hotter microclimates and on average had a 4.2°C (95% CI: 2.7–5.6°C) higher CTmax and 5.3°C (95% CI: 3.5–7°C) broader CTrange than ground‐dwelling ants. This pattern was consistent across the elevation gradient, whether it be the hotter lowlands or the cooler uplands. Across elevation, upland ants could tolerate significantly colder temperatures than lowland ants, whereas the change in CTmax was less pronounced, and CTrange did not change over elevation. Differential exposure to microclimates, due to localized niche preferences, drives divergence in CTmax, while environmental temperatures along the elevation gradient drive divergence in CTmin . Our results suggest that both processes of thermal adaptation and thermal niche asymmetry are at play, depending on the spatial scale of observation, and we discuss potential mechanisms underlying these patterns. Despite the broad thermal tolerance range of arboreal rainforest ants, lowland arboreal ants had the lowest warming tolerance and may be most vulnerable to climate change.